Polygyny and Resources for Empowerment and Equality in Anglo-Phone West Africa: Implications for Childbearing and Women’s Well-Being - Solanke, Bola Lukman; Kupoluyi, Joseph Ayodeji; Abe, John Olugbenga; Bankole, Olatunji Taofik (European Scientific Journal, ESJ, 2018)
In West Africa, polygyny remained a common type of marriage. However, in spite of numerous studies exploring polygyny, the relationship between polygyny and access to resources for empowerment and equality is not well-ascertained in West Africa. This study addresses this gap by raising the question: to what extent does polygyny explains access to resources for empowerment and equality among married women? Data were extracted from 2013 Demographic and Health Surveys in The Gambia, Nigeria and Sierra-Leone. The outcome variable is access to resources for empowerment and equality measured by access to education, employment and barriers to accessing health care. The key explanatory variable is type of marriage with specific attention to polygyny. Multivariate multiple regression was applied using Stata 12. Results showed that polygyny was negatively associated with access to education in the studied countries; positively associated with access to employment in the studied countries; and negatively associated with access to health in Nigeria and Sierra Leone. It is important to refocus national attention to improving the capabilities of women because economic empowerment will not only improve women’s well-being, it will also translate to the reduction of childbearing pressures among women.